Diffusion-Ordered (DOSY) NMR of solute exchange across the human erythrocyte membrane: including an application of Post-Widder Laplace inversion - Chapman, Bogdan E.; Kuchel, Philip W. (Diffusion Fundamentals, 2006)
Nuclear magnetic resonance (NMR) spectroscopy was used to study exchange of three distinctly different molecules across the membranes of human red blood cells (RBCs). In studying water, t-butanol, and dimethyl sulfoxide we exploited the marked differences in the apparent diffusion coefficients of these species inside and outside the cells in suspensions. The measurements were made with diffusion ordered spectroscopy (DOSY) with a domain of ‘diffusion times’ of 20 - 100 ms. In attempting to make the DOSY spectra quantitative we identified time domains for each of the three molecules in which the spectra showed well resolved peaks, and those in which only a single peak was evident for two of the species. The apparent mean resident times for water and t-butanol in the RBCs estimated by the methodology were 17 ms, while the DMSO exchange was too slow, on the NMR timescale, to be quantified by this method. However, it is very clear that other methods that are based on regression analysis with a prescribed fitting function provide more reliable estimates of exchange rate constants. Also, to make the DOSY analysis more generally accessible we implemented a Laplace transform inversion method (the Post-Widder algorithm), and a procedure for enhancing the resolution of the resulting diffusion spectra by using standard functions in Mathematica.